The Effects of Catheter Ablation Therapy on Medication Use and Expenditures in Patients with Atrial Fibrillation - Matthew R. Reynolds; Guy David; Candace Gunnarsson; Jamie L. March; Steven C. Hao (Journal of Health Economics and Outcomes Research)
**Background:** Atrial fibrillation (AF) is the most common cardiac arrhythmia encountered in clinical practice. Catheter ablation has become an important treatment option for many AF patients. Catheter ablation has been hypothesized to reduce the need for continued medical therapy for patients with AF, but there are few empirical data which demonstrate this.